Minimally Invasive Navigated Foraminal Discectomy via Contralateral Approach Using a 3-Dimensional 4K High-Definition Exoscope: 2-Dimensional Operative Video. Issue 2 (24th December 2019) - Oren, Jonathan; Kwan, Kevin; Schneider, Julia; Levine, Mitchell; Langer, David
Abstract: This surgical video is the first to demonstrate a novel minimally invasive technique of utilization of surgically navigated foraminal discectomy using a 3-dimensional 4k high-definition exoscope (Sony Olympus). Typical approaches for foraminal disc herniations may involve violation of the facet resulting in subsequent destabilization requiring fusion. 1 Although minimally invasive facet-sparing contralateral techniques have previously been described, 2 there is continued limitations stemming from rudimentary localization with standard fluoroscopy and impaired visualization with the bulky traditional operative microscope. 3 We demonstrate that high-quality real-time navigation is possible using standard Iso-C intraoperative fluoroscopy for 3-dimensional reconstructions, allowing for intraoperative routing. Navigation is particularly advantageous for adjustments in the trajectory of the tubular retractor and for confirmation of complete foraminal decompression. Visualization from the 4k high-definition exoscope also allows for an unparalleled view of the narrow operative corridor and allows for participation from the operative team. Informed consent was obtained from the patient for the surgery in its entirety.